PEMBERDAYAAN MASYARAKAT MELALUI LITERASI DIGITAL DALAM PENGENALAN DAN PENGEMBANGAN SKILL UNTUK MENGHADAPI ERA DIGITALISASI 4.0 - Taptajani, Dedi Sa'dudin; Muharom, Riyan Padli; Raihan, Muhammad; Al-Zayyan, Syahrul Kustiawan; Bagaskara, Egha Satria; Putri, Puput; Fauziah, Ainun Alvia; Pratama, Chandra; Fedy, Mahesa Al Zidane Putra; Mauludin, Zayan; Syadiah, Magvira Apriliani; Wahyuni, Rahayu Sri; Septiandi, Rizky; Nirmala, Dinneu Siti; Al-Jabbar, Annisa Nur Ilham; Suryana, Latief Dwi; Hadianto, Iqbal Maolana; Fathurrohman, Sidik; Maulana, Rizqi; Afrizal, Nabil Nur (Institut Teknologi Garut, 2023)
This research aims to investigate efforts to empower Sukamanah village communities through digital literacy in the introduction and development of relevant skills to face the Digitalization Era 4.0. This era was marked by significant changes in information and communication technology, which influenced various aspects of human life. Empowering Sukamanah village communities in facing these changes is becoming increasingly important. This study involved collecting qualitative and quantitative data from a number of respondents representing various levels of Sukamanah village society. Effective digital literacy training methods will be explored and evaluated, along with their impact on increasing the knowledge and skills of Sukamanah village communities in facing the challenges of the Digitalization Era 4.0. Apart from that, this research will also analyze the social, economic and cultural factors that influence the success of efforts to empower the Sukamanah village community through digital literacy. It is hoped that the results of this research will provide a clearer view of the role of digital literacy in increasing the capacity of the Sukamanah village community to participate actively in the increasingly digitalized Sukamanah village community. These findings will be a source of insight for policy makers, educators, and various parties interested in advancing the capabilities of Sukamanah village communities in facing the Digitalization Era 4.0.